Transcriptomic Responses of Deep-Sea Corals Experimentally Exposed to Crude Oil and Dispersant - DeLeo, Danielle M.; Glazier, Amanda; Herrera, Santiago; Barkman, Alexandria; Cordes, Erik E. (Frontiers in Marine Science, 2021)
Resource extraction from the ocean comes with ecosystem-wide risks, including threats to its biota such as the habitat forming corals that support elevated biomass and biodiversity. Despite catastrophic incidents like the Deepwater Horizon oil spill (DWHOS) disaster that occurred in 2010, offshore oil and gas drilling continues to occur around the world. Previous work investigating the toxicity of oil and the chemical dispersant used in an attempt to mitigate the effects of the DWHOS revealed that the dispersant elicits a stronger, negative physiological response than oil alone. However, little is known regarding the specific ways in which these anthropogenic pollutants impact organisms at the cellular level. To investigate the impacts of each pollutant and their synergistic effects on corals, we analyzed the transcriptional responses of the deep-sea octocorals Callogorgia delta and Paramuricea type B3 following 12 hours of exposure to oil, dispersant, and mixtures of oil and dispersant. Analyses revealed that the highest levels of significant differential gene expression were found among the treatments containing dispersant, which corresponds to the significant effects observed in physiological experiments. Functional analyses of annotated transcripts further suggest both species- and colony-specific responses to the exposures, likely due to underlying cellular and physiological differences. However, some commonalities were observed among the responses to chemical stress across treatments and species, including immune and cellular stress responses, altered energy metabolism, and oxidative stress, elucidating how corals respond to chemical pollutants. As resource extraction is an ongoing threat, this study demonstrates the importance of considering the varied and diverse responses of biota to anthropogenic disturbances and the implications of introducing chemicals into vulnerable ecosystems like those associated with deep-sea corals.